Transparency and Communication for Chairing a Healthy Department - Robert Williams (Academic Chairpersons Conference Proceedings, 2023)
Explore how to ensure all faculty in the department are engaged as full and participatory individuals whose voices are heard. Topics include: committee composition, scheduling, resolving conflicts, handling difficult faculty, budget works, effective relations across offices, communicating expectations of evaluation and tenuring, supporting faculty initiative, and delegating responsibilitie
Keywords: Respect; Transparency; Communication; Shared Governance; Leadership as Service